Analisa Tingkat Kepuasan Pengguna Aplikasi Absensi B-Gate pada PT. Bank Tabungan Negara Menggunakan Metode Webqual 4.0 - Nia Nuraeni (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Absence is a routine activity carried out by an employee to show that the employee is present or absent at a company, PT Bank Tabungan Negara makes a digitization for attendance, namely making an online B-Gate attendance application. B-GATE online attendance functions to monitor employee work discipline, because by using this system the resulting employee attendance data is very accurate and can be obtained at that time, anytime and anywhere as long as you have an internet connection. As one of the supports in the development of the B-Gate online attendance application, a study was conducted on user satisfaction, namely employees of PT. State Savings Bank for the B-Gate online attendance application using the WebQual 4.0 method. The WebQual method is a quality measurement tool for web-based information systems, to evaluate the level of user satisfaction with the system's services. Data was obtained by distributing questionnaires to employees of PT Bank Tabungan Negara via google form with a total of 105 employees as respondents. Based on the research that has been done, the results show that the quality of use, quality of information and quality of service interaction has a positive and significant effect on user satisfaction. This is proven by the results of the analysis of the average value of the correlation coefficient (r) based on Cronchbach Alpha = 0.838 which gives positive results for each variable on the dependent variable (User satisfaction).